Regional Development And Web 2.0- Applications - Manfred Walser; Ulrich Radzieowski (European Regional Science Association (ERSA), 2010)
The region Walgau is located in the Austrian Federal State of Vorarlberg. The 21 municipalities started a three years development programme to develop common goals and to enhance the intercommunal cooperation. The region is characterized by a dispersed structure of settlement and differences between the more agricultural oriented mountainside and the more industrialized bottom of the valley. For this one of the main goals of process is to establish a regional learning process about different requirements and living conditions. The increasing meaning of the Web 2.0 (social web) is discussed in different fields of politics and society but less in regional development activities. The Web 2.0 means the interactive part of the Internet in which users generate their own environments and issues by communicating, sharing, collecting and co-working. User analyses show that users of different social networks have an average age between 25 and 35 years and represent a generation which weekly is represented in local and regional participation processes. At a first glance it seems promising to use such platforms to enhance the group of activists and to promote the issues of a regional development process. But the experiment also can fail if the target group of such kind of web activities strongly differ from the actors interested in such processes. In this case we have to state that the instrument and the issue fall apart. In the regional development process 'Im Walgau' a regional Wiki starts in January 2010 as an important element of a public discourse on regional development issues. At the ERSA Conference the methodological design of the development process and the concept of communication including the web 2.0- application will be presented and first empirical results of internet participation can be shown.
Keywords: 330